Somatostatin receptor molecular imaging in a misdiagnosed gastrinoma case - Stolniceanu, Cati; Grierosu, Irena; Matovic, Milovan; Stefanescu, Cipriana (World Journal of Nuclear Medicine, 2020)
Gastrin-secreting tumors, hypergastrinemia and severe ulcer disease form the trademarks of Zollinger-Ellison syndrome (ZES). We report a case of gastrinoma, in a patient who was misdiagnosed for almost five years. The case emphsizes the the special role of functional imaging in the personalized approach to the patient with suggestive symptomatology for NETs. Taking into account that in 80 to 100% of cases of gastroenteropancreatic (GEP) NETs are expressing somatostatin receptors, the functional imaging with radiolabeled somatostatin analogues can be used in order to improve its diagnosis, respectively the treatment of GEP NETs. In the approach to the patient with tremendous digestive symptomatology, physicians from different specialties should evaluate NETs specific markers and then insist on structural-functional complementarity, avoiding the waste of time and high cost of repeated structural investigations. The conclusion of our study is that functional imaging is mandatory in the diagnostic algorithm of gastrinoma.
Keywords: Functional imaging; gastrinoma; hypergastrinemia; neuroendocrine tumors; somatostatin receptor scintigraphy